Awareness : The Major Preventive Tools Against Aids - Srivastava, J P (Indian Journal of Community Health, 2005)
AIDS might have started as a bush fire but is now spreading across the world like a forest conflagration that we are finding difficult to extinguish. In a matter of decades the HIV has reached a high level with about 40.3 million affected globally. The year 2005 alone saw an addition of 5 millions with over all estimated adult population below one percent. According WHO and UNAIDS estinates, dispite improved access to anti-Retroviral treatment and the care in many region of the world, the acquired immune defieiency syndrome (AIDS) claimed 3.1 million lives in the year 2005, more than a million of them are children. The AIDS epidemic in India is marked by heterogenecity. The epidemie shift from high risk population to bridge population (Clients of Sex workers, STD patients and partners of drug U'sers) and then to general population. There is timelag of 2-3 years between the shift from one group to another. Currently, the estimated HIV INFECTION RATE among adult population between 15-19 years of age is 0.7%